Effect of Health Literacy on Decision Delay in Patients With Acute Myocardial Infarction - Fan, Zhao-ya; Yang, Yuan; Yin, Ruo-yun; Tang, Lei; Zhang, Fan (Frontiers in Cardiovascular Medicine, 2021)
Background: Health literacy (HL) is a risk factor for adverse outcomes in patients with cardiovascular disease, and shorter pre-hospital delay time is crucial for successful treatment of acute myocardial infraction (AMI) patients. Most previous studies focused on the influencing factors of pre-hospital delay but ignore the essential contribution of decision delay. Aims: Therefore, the purpose of this study was to explore the effect of HL on decision delay. Methods: Continuously included AMI patients admitted to a grade A class 3 hospital in Chongqing. HL level was assessed using Brief Health Literacy Screen and categorized as adequate or inadequate. Mann-Whitney U-test and Chi-square test were used to compare the differences between groups, and binary logistic regression was used to analyze the association between HL and decision delay. Results: A total of 217 AMI patients were enrolled in this study, including 166 males (76.5%) and 51 females (23.5%), with the median age was 68 years old; 135 (62.2%) patients had delayed decision-making while 82 (37.8%) did not; 157 (72.7%) patients had inadequate HL and 59 (27.3%) had adequate HL. The total HL score of non-delayed group was higher than that in delayed group (9.22 VS 7.02, P < 0.000). Conclusion: After adjusting for covariates, HL was significantly negatively associated with decision time. AMI patients with inadequate HL were more likely to delay seeking timely medical care.